El reto de crear bienes culturales en Costa Rica: la producción de libros por parte de las editoriales literarias independientes. - Carballo-Villagra, Priscilla (Revista Espiga)
This article presents the main results from a research carried out during 2017 with independent literary publishing houses in Costa Rica. It proposes an analysis of the production process of books in the country as well as a definition of the main limitations faced by independent publishers.